2017
DOI: 10.1002/slct.201702296
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of 4, 4’‐Oxydianiline Show Distinct In Vitro Cytotoxicity, Apoptosis Induction, and Selectivity against HepG2 Cancer Cells

Abstract: Gathering of number of pharmacophore on a single molecular platform evidently lead to improved therapeutic efficiencies and reduced side effects of conventional chemotherapy drugs. Three diamino precursors 4,4’‐bis(2‐(alkylamino)acetamido)diphenylether (L1‐L3) was selected to derive new series of metallomacrocyclic dithiocarbamate complexes [M2‐μ2‐bis‐{(κ2S,S‐S2CN(R)CH2CONHC6H4)2O}] {R=Cy, M=NiII1a, CuII 1 b, ZnII1c; R=iPr, M=NiII2a, CuII 2 b, ZnII2c; R=nBu, M=NiII3a, CuII 3 b, ZnII3c}. These were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[26][27][28][29][30][31] The unique redox property of the sulfur atom makes it a key residue for enzyme catalysis, protein folding and redox signaling, which are important processes required for cellular energy metabolism, motility and subsistence of cellular systems. [36][37][38][39] Thus, by considering the appreciable in vitro anticancer properties of metallomacrocyclic dithiocarbamate complexes, [40][41][42][43] especially organotin(IV)dithiocarbamates macrocycles, [40] we have selected a number of diamine precursors L1-L5 (Scheme 1) to derivatize them into a new series of binuclear organotin(IV) dithiocarbamate complexes [(Ph 2 Sn) 2 -μ 2 -bis{(κ 2 S,S-S 2 CN(R) Other factors like the ease of synthesis and the effectual binding ability of dithiocarbamate ligands to an eclectic array of metal ions present in different oxidation states of transition/nontransition metal and organometallic building blocks improves the prospects of enhancing the structural modifications of anti-tumor organotin compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] The unique redox property of the sulfur atom makes it a key residue for enzyme catalysis, protein folding and redox signaling, which are important processes required for cellular energy metabolism, motility and subsistence of cellular systems. [36][37][38][39] Thus, by considering the appreciable in vitro anticancer properties of metallomacrocyclic dithiocarbamate complexes, [40][41][42][43] especially organotin(IV)dithiocarbamates macrocycles, [40] we have selected a number of diamine precursors L1-L5 (Scheme 1) to derivatize them into a new series of binuclear organotin(IV) dithiocarbamate complexes [(Ph 2 Sn) 2 -μ 2 -bis{(κ 2 S,S-S 2 CN(R) Other factors like the ease of synthesis and the effectual binding ability of dithiocarbamate ligands to an eclectic array of metal ions present in different oxidation states of transition/nontransition metal and organometallic building blocks improves the prospects of enhancing the structural modifications of anti-tumor organotin compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Dapsone series of compounds showed less toxicity against primary cell line whereas these were potent against the hepatic carcinoma cell line (Hep G2) as well as glioblastoma cell lines (C6). The other reports from our lab highlighted the cytotoxic potentials of metallomacrocyclic compounds bearing biphenyl ether and diphenyl methane linker . The results showed that the compounds are potent against carcinoma (HepG2) cells whereas less toxic against normal (WRL68) cells.…”
Section: Resultsmentioning
confidence: 76%
“…Recently, we have analyzed another three series of compounds having variations on a macrocyclic ligand against hepatic cell line (WERL68) of normal origin as well as hepatic carcinoma (Hep G2). Dapsone series of compounds showed less toxicity against primary cell line whereas these were potent against the hepatic carcinoma cell line (Hep G2) as well as glioblastoma cell lines (C6).…”
Section: Resultsmentioning
confidence: 99%